THE CONSTRUCTION DATE OF THE DOMINICAN CONVENT OF ST OLAF IN TURKU, FINLAND - Immonen Visa; Ratilainen Tanja; Eskola Kari O.; Kinnunen Jussi; Oinonen Markku (Suomen arkeologinen seura, 2025)
The foundation of the medieval Dominican Convent of St Olaf in Turku, South-West Finland, marked the connection of the country to an international network of contacts with the Latin West, and the establishment of taught education in Finland. However, the chronology of its construction has been a subject of scholarly debate since the early 20th century. The archaeological material from the convent is scant, and the only properly datable finds are a sample of timber from the structures and a collection of bricks recovered from the site. In this article we present the results of a wiggle-match dating of the timber, and OSL dating of eight bricks. The bricks were also analysed by pXRF. The building phase of brick masonry seems to date to the second half of the 14th century or around 1400AD.